Two new species of Typton Costa, 1844 from tropical American waters, with taxonomic notes on T. tortugae McClendon, 1911 and a new record of T. granulosus Ayón-Parente, Hendrickx & Galvan-Villa, 2015 (Decapoda: Caridea: Palaemonidae) - Anker, Arthur; Pachelle, Paulo P.g.; Leray, Matthieu (Zootaxa, 2021)
Two new species of the palaemonid shrimp genus Typton Costa, 1844 are described based on material from Panama and Mexico. Both species are closely related to T. tortugae McClendon, 1911, a species originally described from the Dry Tortugas, off southern Florida, USA, and later scarcely recorded from other western Atlantic localities, from Bermuda to Mexico and Brazil. Some clarification and additional illustrations are provided for the type material of T. tortugae. Typton jonkayei sp. nov., is described based on material from fouling-encrusting communities dominated by sponges, growing on submerged roots of the red mangrove, Rhizhophora mangle L., in Bocas del Toro, Caribbean coast of Panama. This new species differs from T. tortugae in several morphological details, for instance, on the minor and major chelipeds (second pereiopods), telson, uropod, frontal margin and ambulatory pereiopods. Typton cousteaui sp. nov. is described based on a single ovigerous female dredged in the southern Gulf of California off Baja California Sur, Mexico, previously reported as T. tortugae. This new taxon seems to represent a true cryptic species with no significant morphological divergence from the allopatrically isolated T. tortugae, except for slight morphometric differences. In addition, T. granulosus Ayón-Parente, Hendrickx & Galvan-Villa, 2015 is recorded from the Pacific coast of Panama, based on material collected in the Coiba Archipelago. Some taxonomic, distributional and ecological remarks are provided for T. granulosus and the closely related T. serratus Holthuis, 1951.